Validation of French upper limb Erasmus modified Nottingham Sensory Assessment in stroke. - Villepinte, C.; Catella, E.; Martin, M.; Hidalgo, S.; Téchené, S.; Lebely, C.; Castel-Lacanal, E.; de Boissezon, X.; Chih, Hui Jun; Gasq, D. (2018)
BACKGROUND: Somatosensory impairment of the upper limb (UL) occurs in approximately 50% of adults post-stroke, associated with loss of hand motor function, activity and participation. Measurement of UL sensory impairment is a component of rehabilitation contributing to the selection of sensorimotor techniques optimizing recovery and providing a prognostic estimate of UL function. To date, no standardized official French version of a measure of somatosensory impairment has been established. OBJECTIVE: To develop and validate a French version of the Erasmus modified Nottingham Sensory Assessment somatosensory (EmNSA-SS) and stereognosis (EmNSA-ST) component for evaluating the UL among adults with stroke. METHODS: This study is a single-center observational cross-sectional study. A French version of the EmNSA for UL was developed by forward-backward translation and cross-cultural adaptation. Fifty stroke patients were recruited to establish concurrent-criterion-related validity, internal consistency, intra- and inter-rater reproducibility with intracorrelation coefficients (ICCs) for reliability and the minimal detectable change with 95% confidence interval (MDC95) for agreement, as well as ceiling and floor effects. Criterion validity was assessed against the Fugl-Meyer Assessment-Sensory (FMA-S) for the UL. RESULTS: The median (range) EmNSA-SS score was 41.5 (1-44). The Spearman rank correlation coefficient between EmNSA-SS and FMA-S total scores was moderate (rho=0.74, P<0.001). The EmNSA-SS/ST internal consistency was adequate across subscales; with Cronbach a ranging from 0.82-0.96. For the EmNSA-SS total score, intra- and inter-rater reliability was excellent (ICC=0.92 in both cases), with MDC95 of 12.3 and 14.6, respectively. EmNSA-SS/ST total scores demonstrated no ceiling or floor effects. CONCLUSIONS: The French EmNSA is a valid and reproducible scale that can be used for comprehensive and accurate assessment of somatosensory modalities in adults post-stroke. Taking less than 30min to administer, the instrument has clinical utility for use in patients with cognitive comorbidities and at various stages of recovery in multidisciplinary clinical practice and research settings.